Human Gut Microbiome – how intestinal bacteria influence our health - Kuźniar, Aleksandra; Szawica, Dominik; Wąsiewicz, Edward; Fularska, Kamila; Oleszko, Michał (Journal of Education, Health and Sport, 2023)
Introduction: Gut microbiome is composed of hundreds of different bacterial species.Possibly every type of bacteria can affect many different aspects of human healthGut bacterial composition varies immensely between healthy and sick people and there are many factors which can influence micriobiota balance in our intestines. Aim of study: The purpose of the study was to review the latest literature on the gut bacteria importance and to discover what factors can influence gut microbiome composition. Matherials and methods: A systemic review was conducted using Google Scholar, PubMed and ScienceDirect databases and the search was limited to studies published between 2000 and 2023. The search strategy was based on following terms: microbiome, gut bacteria, health and microbiome, gut microflora, human intestinal microbiota Results: We found many different studies which show importance of gut microflora in various different ailments and diseases, we have also found many showing factors that influence intestinal microbiota composition.Conclusions: Gut microbiota is very broad topic – it can affect many different aspects of human health, starting from lowering the risk of developing allergy or affecting weight loss to affecting risk of colorectal cancer development . It can be affected by many different factors – lots of them are still uknown and need further studies.